Intact interferon-γ response against Coxiella burnetii by peripheral blood mononuclear cells in chronic Q fever. (March 2017) - Schoffelen, T.; Textoris, J.; Bleeker-Rovers, C.P.; Ben Amara, A.; van der Meer, J.W.M.; Netea, M.G.; Mege, J.-L.; van Deuren, M.; van de Vosse, E.
Abstract: Objectives: Q fever is caused by Coxiella burnetii, an intracellular bacterium that infects phagocytes. The aim of the present study was to investigate whether the C. burnetii -induced IFN-γ response is defective in chronic Q fever patients. Methods: IFN-γ was measured in supernatants of C. burnetii -stimulated peripheral blood mononuclear cells (PBMCs) of 17 chronic Q fever patients and 17 healthy individuals. To assess IFN-γ responses, expression profiles of IFN-γ-induced genes in C. burnetii -stimulated PBMCs were studied in six patients and four healthy individuals. Neopterin was measured in PBMC supernatants (of eight patients and four healthy individuals) and in sera (of 21 patients and 11 healthy individuals). In a genetic association study, polymorphisms in genes involved in the Th1-cytokine response were analysed in a cohort of 139 chronic Q fever patients and a cohort of 220 control individuals with previous exposition to C. burnetii . Results: IFN-γ production by C. burnetii -stimulated PBMCs from chronic Q fever patients was significantly higher than in healthy controls. Many IFN-γ response genes were strongly upregulated in PBMCs of patients. Neopterin levels were significantly higher in PBMC supernatants and sera of patients. The IL12B polymorphisms rs3212227 and rs2853694 were associated with chronic Q fever. Conclusions: IFN-γ production, as well as the response to IFN-γ, is intact in chronic Q fever patients, and even higher than in healthy individuals. Polymorphisms in the IL-12p40 gene are associated with chronic Q fever. Thus, a deficiency in IFN-γ responses does not explain the failure to clear the infection. The genetic data suggest, however, that the IL-12/IFN-γ pathway does play a role.